The Effects of Exergames on Physical Fitness, Body Composition and Enjoyment in Children: A Six-Month Intervention Study - Santo Marsigliante; Giulia My; Gianmarco Mazzotta; Antonella Muscella (MDPI AG, 2024)
Background/Objectives: Physical inactivity in children can lead to decreased physical fitness and reduced enjoyment of physical activity. This study aimed to evaluate the impact of exergaming on physical fitness, body composition and perceived enjoyment in elementary school children. Methods: Sixty-four male students (mean age 9.5 years) were randomly assigned to an exergaming group (EG, n = 32), engaging in Kinect Adventures three times a week for six months, or a control group (CG, n = 32), which continued standard physical education. Assessments were conducted pre- and post-intervention, including anthropometric measures, physical fitness tests (standing long jump, countermovement jump, sit-and-reach, 20-m sprint), aerobic fitness (20-m shuttle run), and perceived enjoyment measured with the PACES scale. Results: The EG demonstrated significant reductions in body weight, BMI, and relative fat mass compared to the CG (p < 0.01). Improvements in physical fitness were evident in EG, with increases in standing long jump distance (+12.8%; p < 0.0001), countermovement jump height (+65%, p < 0.0001), and flexibility (+75%; p < 0.0001). Aerobic fitness improved significantly in EG (+87.8m) compared to CG. Perceived enjoyment was notably higher in EG, especially at week three, compared to CG (69.3 ± 5.8 vs. 44.2 ± 11.6; p < 0.0001). Conclusions: Exergaming offers benefits for physical fitness and body composition in children, while also enhancing enjoyment. Incorporating exergames into physical education programs could be an effective strategy for addressing childhood obesity, improving physical skills, and increasing student enjoyment, encouraging long-term physical activity adherence.